Pengembangan Media Pembelajaran Berbasis Problem Based Learning Menggunakan Canva di Kelas X TKJ pada Mata Pelajaran Orientasi Dasar Teknik Jaringan Komputer dan Telekomunikasi di SMK 3 Padang - Megasyani Anaperta; Kurniasih Kurniasih; Topan Saputra; Aidil Fitra Hadi; Agra Wiratama (Jurnal Sains dan Teknologi, 2023)
This research was conducted due to the lack of optimal use of interesting media, as well as the lack of teacher skills in using digital-based media in the learning process. Because of this, students often become bored and lose interest in learning lessons. As a result, learning materials tailored to students' interests and preferences are needed.One way to achieve this is by creating the development of Problem Based Learning Media using Canva for class X TKJ in basic computer network and telecommunications orientation subjects at SMK N 3 Padang. The aim of implementing Canva as a learning medium can be a creative solution to increase student focus by visualizing material in an interesting and interactive way. This type of research uses Research and Development (R&D), and the development model used is 4D model design. This 4D development model consists of four stages, namely Define, Design,Develop (Development) and Disseminate (Dissemination). Research carried out at SMK N 3 Padang, research findings produced learning materials with material validity of 89.07% and media design validity of 93.7% and teacher response questionnaire answers of 96.6% and the student questionnaire response was 88.12 which can be categorized as very valid and practical.